Pengaruh Ekstrak Daun Teh (Camellia sinensis, Linn. var. Assamica) terhadap Mortalitas Cacing Ascaris suum, Goeze - Afiyyuddin N, Ahmad; Utari, Cr. Siti; Wijayanti, Lilik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Camellia sinensis, Linn. var. Assamica leaves contain tannin that have been known to have anthelmintic effect. This study aimedÂ to determine the effect of Camellia sinensis, Linn. var. Assamica leaves extract toward death time of Ascaris suum, Goeze. Methods: The study was a laboratory experimental research using the post-test only controlled group design. Subjects were Ascaris suum, Goeze. The sampling technique used was purposive random sampling. Subjects were divided into 7 groups, each group using 4 worms, replication performed 5 times. Saline solution was used in negative control group, pirantel pamoate 5 mg/ml was used in positive control group, while the treatment group used Camellia sinensis, Linn. var. Assamica leaves extract concentration of 50%, 60%, 70%, 80%, and 90%. Worms immersed in the test solution at 25 ml and incubated at 37Â°C. Observations were made every 1 hour and counted dead times of all worms. Data were analyzed with regression linier and probit analysis. Results: Observations of total deaths mean time Ascaris suum, Goeze negative control for 48 hours, the positive control 1 hours 10 minutes, the concentration of 50%, 60%, 70%, 80%, 90% for 10 hours 24 minutes, 9 hours 12 minutes, 7 hours 12 minutes, 5 hours 12 minutes and 4 hours. Linear regression test results show that the variation of the concentration affects long worm death. Probit analysis results obtained LC50 and LT50 Camellia sinensis, Linn. var. Assamica leaves extract is 67,183% and 3 hours 46 minutes. Conclusions: Based on this study, it can be concluded that of Camellia sinensis, Linn. var. Assamica leaves extract affects mortality of Ascaris suum, Goeze, the increasing of extract concentration is inversely proportional with the death time of worms. Keywords: Camellia sinensis, Linn. var. Assamica leaves extract, Ascaris suum, Goeze.Â